Diet of the Golden Eagle Aquila chrysaetos in two areas on the southern slopes of the Catalan Pyrenees - Mañosa, Santi; Gracia, Edu; Claramunt, Bernat; Canut, Jordi; Figueroa, Irene; Margalida, Antoni (Universidad Autónoma de Barcelona, 2021)
[EN]: We provide quantitative information regarding the diet of the Golden Eagle Aquila chrysaetos during the breeding season in two different areas on the southern slopes of the Catalan Pyrenees (NE Spain). Food remains and pellets were collected at nests after chicks had fledged in two study sites, Pallars and Cerdanya, on central and eastern Pyrenees respectively. Six territories were sampled in Pallars in 2001–2005 and four in Cerdanya in 2008, totalling 11 and four territory·year diet samples respectively, from which 205 prey items were identified. In Cerdanya, 44% of prey items were Hares, Rabbits or Marmots, 18% ungulates, 11% corvids and 9% small passerines, followed by 4% small mammals, 4% gamebirds, 2% carnivores and 2% pigeons. In Pallars, only 21% of prey items were Hares, Rabbits or Marmots, 15% were ungulates, 9% corvids and 4% small passerines. However, the eagles in Pallars consumed larger amounts of other prey types: 17% small mammals, 11% carnivores, 10% gamebirds, 4% pigeons and 4% birds of prey. The Ptarmigan Lagopus muta, a target species of conservation concern, accounted for 2.4% of all prey. Our results suggest that, in areas where eagles prey, above all, on Hares and Marmots, their dietary diversity was lower, whereas in areas where these prey types were less frequently captured, the prey-size distribution was more left-skewed and dietary diversity increased. The capture of small and medium sized predators was more frequent in the area where the intake of Hares and Marmots was lower. The adjustment in the consumption of meso-predators as a function of the availability of the main prey types may have effects on the regulation of the whole community. [ES]: Presentamos nueva información cuantitativa sobre la dieta del águila real durante la época de cría en la vertiente sur del Pirineo catalán. Recolectamos restos de presas y egagrópilas en nidos después del vuelo de los pollos, en dos zonas de estudio, Pallars y Cerdanya, situadas en el Pirineo central y Pirineo oriental respectivamente. ...